A fluorescence in situ staining method for investigating spores and vegetative cells of Clostridia by confocal laser scanning microscopy and structured illuminated microscopy. (July 2018) - D'Incecco, P.; Ong, L.; Gras, S.; Pellegrino, L.
Graphical abstract: Highlights: A new Hoechst/Propidium iodide stain for microscopy of Clostridial cell and spores. Fluorescent probes can be combined to inform on cell structure and viability. This novel direct staining for spores in cheese breaks barriers to in situ studies. Abstract: Non-pathogenic spore-forming Clostridia are of increasing interest due to their application in biogas production and their capability to spoil different food products. The life cycle for Clostridium includes a spore stage that can assist in survival under environmentally stressful conditions, such as extremes of temperature or pH. Due to their size, spores can be investigated by a range of microscopic techniques, many of which involve sample pre-treatment. We have developed a quick, simple and non-destructive fluorescent staining procedure that allows a clear differentiation between spores and vegetative cells and effectively stains spores, allowing recovery and tracking in subsequent experiments. Hoechst 34580, Propidium iodide and wheat germ agglutinin WGA 488 were used in combination to stain four strains of Clostridia at different life cycle stages. Staining was conducted without drying the sample, preventing changes induced by dehydration and cells observed by confocal laser scanner microscopy or using a super-resolution microscope equipped with a 3D-structured illumination module. Dual staining with Hoechst/Propidium iodide differentiated spores from vegetative cells, provided information on the viability of cells and was successfully applied to follow spore production induced by heating. Super-resolution microscopy of spores probed by Hoechst 34580 also allowed chromatin to be visualised. Direct staining of a cheese specimen using Nile Red and Fast Green allowed in situ observation of spores within the cheese and their position within the cheese matrix. The proposed staining method has broad applicability and can potentially be applied to follow Clostridium spore behaviour in a range of different environments.